The military aspects of the foreign policy of the United States in Southern Africa from 1975 to t1995 : the military aspects,from Covert actions and military interventions to Capacity Building. - (:unkn) unknown (My University, 2017)
The United States has been traditionally accused of having no real African policy. A period seems to avoid this statement because it was particularly rich in this domain. It is the period covering the years 1975 to 1995 and particularly the Southern Africa area. This foreign policy has however been fluctuating according to presidencies and influenced so much by the cold war and by the imperatives of national politics.After the collapse of the Portuguese empire, the United States have been taken by surprise in this strategic region in various areas. With the end of the Vietnam war, Cuba and the USSR launched an expansionist policy in Africa. These two parameters will create the conditions for a resurgence of interest of this region and give South Africa a key role when public opinions started to be more engaged against apartheid.The features and components of this policy, the decision-making process with multiple and varied actors are a particularly rich subject of study. What is the real part of the regional approach to a more holistic one? What are the specificities of Democratic and Republican administrations?At the military level, there has been some leniency towards the South African nuclear and biological program and the maintenance of the strong linkage between the military of both countries. The use of the CIA's covert operations, Mobutu’s Zaire support, NATO's involvement and the resistance of the frontline states are all aspects of this rich history.
Keywords: African Research